امام محمد بن نصر مروزی رحمۃ اللہ علیہ (متوفیٰ 294 ھ)کی علمی زندگی (عصر حاضر کے تناظر میں): Scholarly Life of Imam Muhammad bin Nasr Maroazi (Died 294 AH) In the Contemporary Context - Dr. Muhammad Wajeeh Ud Din Nouman; Prof. Dr Hafiz Muhammad Inam Ullah (Al Manhal Research Journal, 2024)
Imam Muhammad bin Nasr Marwozi (may Allah have mercy on him) was born in Baghdad He loved religion in his life, it is known about him that if he talked to a person in his life, he only talked about knowledge, his talk was based on knowledge, and when the knowledge conversation ended So he used to leave this assembly, he used to get some stipend from the people of Samarkand for living, but whatever was left over from necessity, he spend it on the poor and the needy. He was always generous, and his thought was that Allah loves generous people. Hafiz Ibn hajar, may Allah have mercy on him, used to say that Imam Marwozi, may Allah have mercy on him, had a strong memory. He had his place in the knowledge of hadith, Allama Dhahbi. May Allah have mercy on him, he also used to praise Imam Marozi, may Allah have mercy on him, for his strong memory. He was considered the Grand Mufti of Nishapur, when there was a problem of jurisprudence, he was always consulted about the issue. His genealogy is not mentioned in the books. His great muhaddith teachers include Ibrahim bin Mundhir, Abu Qudama Sarkhsi, Ishaq bin Rahawiya, Muhammad bin Abdullah, Muhammad bin Abdul Malik, and Rabi bin Sulaiman, may Allah mercy on them. Man can get a wider knowledge of religious facts, modern activities, and inventions and can expand the boundaries of knowledge.